Chemical synthesis of germanium nanoparticles with uniform size as anode materials for lithium ion batteries. Issue 7 (27th January 2016) - Wang, Liangbiao; Bao, Keyan; Lou, Zhengsong; Liang, Guobing; Zhou, Quanfa
Abstract : A simple Mg-thermal reduction reaction is reported to synthesize germanium (Ge) nanoparticles with a uniform size at a low temperature of 400 °C in an autoclave. Abstract : A simple Mg-thermal reduction reaction is reported to synthesize germanium (Ge) nanoparticles with a uniform size at a low temperature of 400 °C in an autoclave. The as-prepared Ge nanoparticles exhibit promising anode applications in lithium ion batteries with high capacity and excellent cycling stability.